Ecocentric and anthropocentric settings as determinants of youth social maturity and eco-culture development - Vіacheslav Zasenko; Liana, Onufriieva; Oksana, Chaikovska; Lesya, Prokhorenko; Myroslava, Sadova (International Journal of Psychosocial Rehabilitation, 2020)
The article presents results of theoretical and empirical analysis of problems ecocentrism as the conditions of social maturity of the individual and the ecological culture of future specialists. The authors considered ecocentrism as a socio-psychological phenomenon that implies a conscious attitude to the environment and improve the quality of the natural environment through changes to human activities from destruction of nature to redefining political, environmental and social organizations aimed at rethinking the relationship between nature and man. Described and characterized the structural components of ecological consciousness. During the empirical research of the interrelation between indicators Express ecocentrism and signs of social maturity of the individual students. It is determined that the level of development ecocentrism installations of student’s youth determines the content of their social maturity, which is accompanied by relevant personal and behavioral properties. Experimentally proved, that for students with a strong level ecocentrism plants to the environmental condition’s characteristic traits of sociability, balance, openness and extroversion. Discovered the relationship between indicators Express ecocentrism and signs of social maturity of the individual students indicates improvement of the model of formation of ecological culture of future specialists, the development of appropriate training and methodological support of formation of ecological culture.